Synchronous cervical sympathetic chain schwannoma, parathyroid adenoma and hypofunctional nodular goiter - a case report and literature review - Flaviu Muresan; Alexandrina-Manuela Muresan; Gabriel-Emil Petre; Iacob Domsa; Vasile Ovidiu Fabian; Olga Hilda Orasan (Journal of Mind and Medical Sciences)
Simultaneously diagnosing cervical sympathetic chain schwannoma, nodular goiter and parathyroid adenoma is a very rare event during clinical practice. We had the opportunity to find this unusual association on a female patient. While nodular goiter and parathyroid adenoma are more common diseases and easier to diagnose, identifying the etiology of a parapharyngeal space tumor remains a challenge and requires multiple imaging studies such as computed tomography scan, magnetic resonance imaging or angiography. A cervical sympathetic chain schwannoma, a carotid body tumor, a paraganglioma or a vagal schwannoma must be taken into account as possible diagnostic variants. Complaints such as Horner`s syndrome, hoarse voice or dysphagia may suggest a nerve originating tumor, but this is a rare situation. Only the surgical exploration is successful in detecting the tumor origin from the cervical sympathetic chain. Even so, the exact origin of the tumor cannot usually be detected without surgical exploration and removal of the piece or biopsies. Therefore, the pathological report of the specimen (adding or not immunohistochemistry tests) is mandatory to be able to confirm the diagnosis of schwannoma.